Władysław Strzemiński – powieściopisarz? - Kmiecik, Michalina ((Dy)fuzje: Związki literatury i sztuki w Polsce po 1945 roku, 2019)
Władysław Strzemiński, a painter and art theoretician, is still relatively unknown as the author of literary texts. His interest in literature, however, seems to be wide: he made graphic design for poetic volumes (above all, Z ponad by Julian Przyboś), was fascinated by functional printing, considered a book was an art object. Janusz Zagrodzki also ascribes to him the authorship of the volume Motorem słów. His unfinished novel, which is analysed in this article, seems interesting today for several reasons. Written by Strzeminski in the 1940s, it portrays the world’s disintegration during the Holocaust. At the same time, we can read it as a clear echo of avant-garde poetics, social and ideological postulates of the new art. Strzemiński as a writer stubbornly defends the rules applicable in the world from before the catastrophe, though he is aware of all dangers they carry with them.